Adoption of Improved Technologies Among Nagpur Mandarin Growers in Vidarbha - Vinod Anavrat (Indian Journal of Extension Education, 2015)
Nagpur mandarin (Citrus reticulata Blanco) popularly known as ’Nagpur Orange’ has got a Geographical Indication (GI) tag identity. Besides the Vidarbha region of Maharashtra, it is grown in the three districts of Rajasthan and Madhya Pradesh. Being a cash crop, mandarin cultivation in Maharashtra increased upto 1,35,000 ha and occupies top position in terms of area. However, the average productivity of 9-10 tons/ha point at the dismal status of Nagpur mandarin industry especially in Vidarbha. Hence, to ascertain the causes of technology non-adoption leading to low productivity, the study was undertaken in the Nagpur mandarin growing area of Central India comprising 300 respondents in a stratified random sampling. The study revealed that, growers with land large holdings were better adopters due to increased scientific orientation and better extension contacts. Overall, the reason of non-adoption differed with the perceived importance of technology by the respondents. However, lack of information was one of the major handicaps and the growers need to be equipped with required information for accelerating the improved technology adoption process.